Local journalism as civic infrastructure: jubi's practices in countering misinformation and disinformation in Papua - Mawara, Ricky Engel (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2026)
The rapid development of the digital information ecosystem in the 21st century has opened pathways for misinformation and disinformation to circulate widely across societies, including in regions that remain peripheral to mainstream academic inquiry, such as Papua. As the fourth estate of democracy and a cornerstone of civic infrastructure, mass media carries substantial responsibility in maintaining the integrity of public information — a responsibility that weighs more heavily at the local level, where communities are disproportionately exposed to information disorders. This study examines the role and strategies of Jubi, a local media outlet based in Papua, in detecting, verifying, and countering misinformation and disinformation within the public sphere. Drawing on a qualitative case study design, data were gathered through in-depth interviews with field journalists, editors, and senior editorial staff at Jubi, alongside direct observation of newsroom practices and thematic analysis of published news documentation. Results indicated that Jubi maintains a consistent commitment to fact-checking and clarification as core mechanisms for ensuring informational accuracy. The study also found that audience emotion and psychological disposition constitute significant drivers in the spread of false information, making contextually grounded and socially sensitive journalistic approaches central to effective verification. These findings contribute to the growing literature on local journalism in eastern Indonesia and suggest that local media outlets are capable of functioning as agents of social mitigation amid the increasingly intricate challenges of today's information environment.